Acute cytokine treatment stimulates glucose uptake and glycolysis in human keratinocytes. (January 2023) - Holt, Vance; Morén, Björn; Fryklund, Claes; Colbert, Robert A.; Stenkula, Karin G
Abstract: During inflammation, cellular glucose uptake and glycolysis are upregulated to meet an increased energy demand. For example, keratinocyte glycolysis is essential for progression of psoriasis. Therefore, understanding the regulation of glucose metabolism in keratinocytes is of importance. Here, we show that the pro-inflammatory cytokines IFNγ and TNF together rapidly induce glucose uptake, glycolysis, and glycolytic capacity in cultured keratinocytes. Furthermore, we found that acute IFNγ and TNF stimulation induces glucose transporter 4 (GLUT4) translocation to the plasma membrane and engages AMPK-dependent intracellular signaling. Together, these findings suggest acute cytokine-induced glucose metabolism in keratinocytes could contribute to inflammation in psoriatic disease, and that GLUT4 is involved in these processes.